Long-Term Outcomes After Treatment With a Paclitaxel-Coated Balloon Versus Balloon Angioplasty: Insights From the PEPCAD-DES Study (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent Please Paclitaxel-Coated Percutaneous Transluminal C - Rittger, Harald; Waliszewski, Matthias; Brachmann, Johannes; Hohenforst-Schmidt, Wolfgang; Ohlow, Marc; Brugger, Andreas; Thiele, Holger; Birkemeyer, Ralf; Kurowski, Volkhard; Schlundt, Christian; Zimmermann, Stefan; Lonke, Sandra; et al. (Jacc-Cardiovascular Interventions, 2015)
The intention this PEPCAD-DES (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent Please Paclitaxel Eluting Percutaneous Transluminal Coronary Angioplasty [PTCA] Catheter) study update was to demonstrate the safety and efficacy of paclitaxel-coated balloon (PCB) angioplasty in patients with DES-ISR at 3 years.In the PEPCAD-DES trial late lumen loss and the need for repeat target lesion revascularization (TLR) was significantly reduced with PCB angioplasty compared with plain old balloon angioplasty (POBA) in patients with drug-eluting stent in-stent restenosis (DES-ISR) at 6 months. We evaluated whether the clinical benefit of reduced TLR and major adverse cardiac events (MACE) was maintained up to 3 years.A total of 110 patients with DES-ISR in native coronary arteries with reference diameters ranging from 2.5 mm to 3.5 mm and lesion lengths <=22 mm were randomized to treatment with either PCB or POBA in a multicenter, randomized, single-blind clinical study. With a 2:1 randomization, 72 patients were randomized to the PCB group and 38 patients to the POBA group. At baseline, there were lesions with at least 2 stent layers in PCB (52.8%, 38 of 72) and POBA (55.3%, 21 of 38) patients.At 36 months, the TLR rates were significantly lower in the PCB group compared with the POBA control group (19.4% vs. 36.8%; p = 0.046). Multiple TLRs in individual patients were more frequent in the POBA group compared with the PCB group (more than 1 TLR: POBA, 13.2%; PCB, 1.4%; p = 0.021). The 36-month MACE rate was significantly reduced in the PCB group compared with the POBA group (20.8% vs. 52.6%, log-rank p = 0.001).PCB angioplasty was superior to POBA for the treatment of DES-ISR patients in terms of MACE and TLR for up to 36 months. There was no late catch-up phenomenon. (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent® Please Paclitaxel Eluting Percutaneous Transluminal Coronary Angioplasty [PTCA] Catheter [PEPCAD-DES]; NCT00998439).
EVALuna2:12089